THE ROLE OF THE HOSPITALITY INDUSTRY IN ACHIEVING SUSTAINABLE TOURISM DEVELOPMENT BY APPLICATION TO FIRST-CLASS HOTELS IN THE CITY OF ERBIL - Shakir Mahmood Awad; Naser Nazar Mohamed Raof (Scholars Digest Publishing, 2024)
The study aimed to determine the relationship of correlation and impact between the independent variable (hospitality industry) and its dimensions represented by (global instability, seasonality, costs, labor) in the dependent variable (sustainable tourism) and its dimensions represented by (economic, environmental, social) and the study relied on the descriptive analytical approach in data analysis and the questionnaire form was used as a main tool for research in data collection, that was distributed (37) form to workers in a group of hotels in the city of Erbil and retrieved (34) form and after examining the forms found that (2) . Forms not valid for analysis and became valid forms for analysis (32) The research reached a number of conclusions, most notably: The results of the study revealed a correlation between the dimensions of the hospitality industry and the dimensions of sustainable tourism development at the level of the hotels surveyed, noting that the process of association extended to embody each dimension of the hospitality industry sustainable tourism development and concluded the research endeavor with a number of proposals, the most important of which are: Increasing the interest of hotel management in the contents of tourism administrative thought because of its contribution to enhancing their ability to overcome the challenges they face and reach success and growth, and this is done through the preparation of an updated program on the developments reached by competing hotels, provided that this program includes a set of seminars, seminars and workshops with hosting a group of specialists in the field of tourism and etiquette in Iraqi institutes and universities
Keywords: hospitality industry, tourism, instability, seasonality, costs.